DOI: 10.31274/rtd-180813-17010
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of agricultural extension educators regarding livestock waste management education in the North Central Region

Abstract: This dissertation is dedicated to the Most High God my creator and savior, without whose grace, power and wisdom I would not have reached this height in my academic pursuit; and to my parents, whose upbringing, love and support constantly sustained my early childhood, secondary and university education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 74 publications
3
17
0
Order By: Relevance
“…This study is based on field research carried out in Libya in 2017. The quantitative method applied in this study is to make it more reliable through research questionnaire adopted from Kwaw-Mensah [15], articles, textbooks, and studies on the subject and internet source.…”
Section: Research Modelmentioning
confidence: 99%
“…This study is based on field research carried out in Libya in 2017. The quantitative method applied in this study is to make it more reliable through research questionnaire adopted from Kwaw-Mensah [15], articles, textbooks, and studies on the subject and internet source.…”
Section: Research Modelmentioning
confidence: 99%
“…In his study, Kwaw-Mensh (2008) found that 76.3 % of the extension educators in the North Central Region who responded to his study were male. In the similar studies, Camara However, in this research study, the target population was all extension educators in the North Central Region including the extension educators with on-campus faculty responsibilities.…”
Section: Demographic Characteristicsmentioning
confidence: 91%
“…The review of literature indicates that there has been no known research conducted on the food safety educational processes used by extension educators either in the NCR or anywhere else in the United States. There have been some studies that studied the perceptions of extension educators toward the educational processes related to livestock waste management (Kwaw-Mensah, 2008), water quality issues (Camara, 2006), and sustainable agriculture (Jayaratne, 2001) but there is no known study that has compared and contrasted the results among the 12 states in the NCR. Also, there is no known research study that has identified the food safety educational process related inservice needs of the extension educators.…”
Section: Need For the Studymentioning
confidence: 99%
“…Coming to the extension educators' preferences regarding the teaching methods and tools, Kwaw-Mensah (2008) found that extension educators perceived one-on-one instruction and demonstrations to be effective in educating farmers about livestock waste management. Camara (2006) found similar results researching extension educators' perceptions regarding the teaching learning processes about water quality issues (Camara, 2006).…”
Section: Adult Educationmentioning
confidence: 99%
See 1 more Smart Citation